Métodos anticonceptivos como medida de prevención Del embarazo adolescente: conocimientos y actitudes En estudiantes del quinto año de educación secundaria De la I.E “San Juan de Maynas” distrito y provincia de Moyobamba – San Martin, Julio – Octubre 2015 - Valdivieso Angulo, Ruth Evelyn (2015)
This study aimed to determine the relationship between the level of Knowledge and attitude towards the use of contraceptive methods as Prevention of teen pregnancy in the fifth year students of secondary EI San Juan de Maynas district and province of Moyobamba, San Martin Department. Period: July-October 2015, quantitative descriptive Correlational cross-sectional study. The sample was composed of 125 Students, who met the inclusion and exclusion criteria. To measure the Variables level of knowledge and attitude towards the use of Contraceptive methods, it was used as the survey method and a checklist Was used to corroborate the student's attendance and enrollment. The results were: The level of knowledge about the attitude towards Contraceptive use stood at an average level with 79.2% and 19.2% Conceptualized at a high level, attitude toward the use of contraceptives Was indifferent to 57.6%. The most used by students in the fifth year of Secondary education was obtained contraception 40.0% used a condom. In conclusion there is a significant relationship between the average level Of knowledge 79.2% and 48.8% indifferent attitude towards the use of Contraceptive methods.